Oil-in-water camellia seeds oil nanoemulsions via high pressure microfluidization: Formation and evaluation. (April 2021) - Li, Long-Wei; Chen, Xiao-Yi; Liu, Lan-Cong; Yang, Yi; Wu, You-Jiao; Chen, Gang; Zhang, Zhi-Feng; Luo, Pei
Abstract: Background: Camellia seeds oil (CSO) is an edible oil which easily oxidises and turns rancid when exposed to air. The purpose of this study was to produce stable CSO nanoemulsions to increase their stability and bioactivity. Method: Under optimized oil/surfactants ratios, surfactants formulated and stabilized CSO nanoemulsions via optimized pressures and chemical components of CSO were analyzed by GC-MS. Bioactivity assessments were performed by using sepsis model and antimicrobial tests. Results: The droplet diameter was 47.81 ± 0.78 nm, PDI was 0.143 ± 0.011, and zeta potential was −6.92 ± 0.94 mV. The nanoemulsions exhibited monomodal size distributions. Antimicrobial properties of nanoemulsions were determined by MIC against Escherichia coli cells was 200 mg/mL. Oral administration of CSO nanoemulsions could significantly improve the survival rate of endotoxemic mice. Conclusion: Our results suggest the application of CSO nanoemulsion may be exploited in aqueous systems for extending the functional or medicinal properties. Highlights: Camellia seeds oil nanoemulsions were prepared by high pressure microfluidization. Stable CSO nanoemulsions were spherical shape with a diameter of 47.81 ± 0.78 nm. CSO nanoemulsions have a good antibacterial activity. CSO nanoemulsions have a good effect in treating sepsis induced by LPS.